Value of a Low Lactose Special Formula in the Management of Acute Infantile Gastroenteritis - Roghani, Mehr Taj; Akhtar, Tasleem; Ramzan, S. (Journal of Postgraduate Medical Institute, 2011)
Seventy five children with acute diarrhea were randomly allocated to three groups of 25 each to evaluate the effectivity of newly introduced low lactose, low fat and high protein nutritional supplement for children suffering from acute infantile gastroenteritis. The special formula was statistically significantly better than cow's milk based formula and Soya based lactose free formula in the period of normalization of stools, number who had normal stools, weight gain during stay in hospital, recurrence of diarrhea and weight gain after discharge from hospital.